PUBLIC SERVICES IN WONOHARJO VILLAGE PANGANDARAN DISTRICT PANGANDARAN REGENCY - Elva Tiana; Otong Husni Taufiq (JGSRD: Journal of Government Science and Rural Development, 2021)
This research is motivated by the effectiveness of management information systems in public services in Wonoharjo Village, Pangandaran District, Pangandaran Regency is still not optimal. Based on the above background, the purpose of this study is to determine the effectiveness of management information systems in public services in Wonoharjo Village, Pangandaran District, Pangandaran Regency. The research method used in this study is a qualitative research method. The duration of the research that the authors did was approximately 9 months. In this study, there were 5 informants. The data collection tools are library research, field studies (observations and interviews). The results showed that: The effectiveness of management information systems in public services in Wonoharjo Village, Pangandaran District, Pangandaran Regency has not been implemented properly in accordance with Makmur's opinion in Sawir (2020:126) regarding effectiveness in an organization. This is evidenced by the lack of understanding of the village government regarding management information systems related to the implementation of management information systems, the lack of human resources for village officials who understand management information systems to support improving the quality of public services and the impact of change for the community has not been fully implemented properly. There are obstacles to the effectiveness of management information systems in public services in Wonoharjo Village, Pangandaran District, Pangandaran Regency This is due to the lack of ability and understanding of the village government towards management information systems, lack of budget in the implementation of public services so that there is no visible improvement in public services, lack of awareness of the village government on the ability and understanding of management information systems to improve public services. The existence of efforts to overcome obstacles to the effectiveness of management information systems in public services in Wonoharjo Village, Pangandaran District, Pangandaran Regency, this is done by increasing the understanding of village officials in the implementation of management information systems by participating in training so that the implementation of services carried out can run optimally and can that are perceived by the public as visible. In addition, by increasing the participation of the village government in the implementation of management information systems by providing direction and guidance so that implementation looks optimal